Ações que Contribuem com o Desenvolvimento de Municípios do Sul de Minas Gerais - Leandro Rivelli Teixeira Nogueira (Universidade Regional do Noroeste do Estado do Rio Grande do Sul, 2018)
About 81% of municipalities in Brazil are essentially rural. In many cases, the local development is guaranteed by the rural development. Actions focused in the intention for the development should target effort to these places for the strengthening of family farming because, a mean of about 84% of farms are of family farmers. Thus, the present work was performed aiming to assess actions focused to the family farming, which contribute to the development of the municipalities of Southern of the State of Minas Gerais. The research was conducted with the family farmers in 15 municipalities in southern Minas Gerais, totaling an application of 205 structured questionnaires. For data analysis, we used regression analysis. Therefore, it highlights here the importance of actions focused to the family farming, which can give alternatives for the commercialization of agricultural surplus. In addition, the existence of actions which can provide technical and management guidance to the family farmers becomes essential, what can enable them to obtain better yields, as well as the development of their municipalities.